2021
DOI: 10.33714/masteb.627562
|View full text |Cite
|
Sign up to set email alerts
|

Population, Aquaculture and Transplantation Applications of Critically Endangered Species Pinna nobilis (Linnaeus 1758) in the Mediterranean Sea

Abstract: The population of fan mussel, Pinna nobilis across the Mediterranean Sea has been affected by factors such as overfishing, fisheries processes, environmental pollution, destruction of habitat, tourism, etc. Therefore, the species P. nobilis was taken under protection by the Decisions of the Council of Europe and Barcelona Convention. However, its mortality rates of 100% have been reported to be due to Haplosporidium pinnae, a parasite in different Mediterranean regions. The status of P. nobilis has thus been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Transplantations have been suggested to be responsible for the absence of geographic structure of Mytilus galloprovincialis populations in the Aegean Sea ( Giantsis, Kravva & Apostolidis, 2012 ). This might have been the case also for P. nobilis , as transplantations had been proposed as a conservation action for the protection of the species ( Katsanevakis, 2016 ; Acarli, 2021 ), although they were most likely performed only on a local scale and, thus, they should not have influenced the genetic structure of P. nobilis at the scale of the Aegean Sea. However, since they were not documented in detail, it is impossible to fully assess their potential effect on the populations.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantations have been suggested to be responsible for the absence of geographic structure of Mytilus galloprovincialis populations in the Aegean Sea ( Giantsis, Kravva & Apostolidis, 2012 ). This might have been the case also for P. nobilis , as transplantations had been proposed as a conservation action for the protection of the species ( Katsanevakis, 2016 ; Acarli, 2021 ), although they were most likely performed only on a local scale and, thus, they should not have influenced the genetic structure of P. nobilis at the scale of the Aegean Sea. However, since they were not documented in detail, it is impossible to fully assess their potential effect on the populations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Basso et al (2015) documented that there was a decreasing trend in the number of individuals with increasing depth, with higher densities in the first 10-12 m. It has also been observed that P. nobilis densely distributed in seagrass habitats while scarce or no population has been observed in gravelly or sandy habitats. Many researchers have reported the dense distribution of P. nobilis populations within seagrass meadows (Coppa et al, 2010;Basso et al, 2015;Tatton et al, 2019;Acarli, 2021;Acarlı et al, 2021). Basso et al (2015) compared 24 scientific papers based on 77 observations and noted that P. nobilis were most frequently observed in P. oceanica beds with an average of 8.06±2.35 ind./100 m 2 , while in Cymodocea meadows with averages of 11.06±1.82 ind./100 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The culture of fan mussels in captivity has complications related to the small number of individuals to work with, their large size, which reduces the number of individuals that can be maintained in tanks, and the impossibility of growing collected seed in suspended culture in the open sea, as had been done priors to the mortality event (Kozul et al, 2012; Acarli, 2021). These circumstances make it necessary to find alternative solutions to obtain gametes and work on larval settlement as a key objective to close the life cycle in captivity.…”
Section: Discussionmentioning
confidence: 99%